A development curse: formal vs informal activities in resource-dependent economies. Issue 3 (4th March 2014) - Papyrakis, Elissaios
Abstract : Purpose: – The paper aims to examine the coexistence of formal and informal resource sectors in resource-dependent economies, whose production depends on an exhaustible (e.g. minerals) and a renewable resource stock (e.g. forest), respectively. It then examines the implications of declining mineral stocks on public revenues, labour movements between sectors, and economic growth in an attempt to elucidate the poor economic performance of many mineral-dependent countries. Design/methodology/approach: – The paper presents a theoretical model that describes the coexistence of a formal and informal resource-dependent sector, where individuals can direct their work effort. It then assesses how declining mineral stocks influence labour mobility across sectors and environmental degradation. Findings: – Decreasing mineral stocks induce a relocation of labour towards informal production and deprive local authorities from public revenues collected within the formal economy. This constrains the ability to improve infrastructure and welfare over time and simultaneously imposes pressure on the local environment. Originality/value: – The paper provides a novel theoretical mechanism that attempts to elucidate the "resource curse", i.e. the poor economic performance of many mineral-rich economies. It purposely explores the implications of a coexistence of formal and informal resource activities on economic development for resource-dependent economies, in order to obtain new insights into this direction.